Basics of Academic Writing in English - Bhandari, Bhim Lal; Bhandari, Sabina (Kaladarpan कलादर्पण, 2025)
Writing an academic paper is a challenging task that demands advanced linguistic skills and adherence to the standards of academic writing in higher education. Academic writing is a formal, structured, and evidence-based mode of communication designed to convey knowledge objectively and persuasively within scholarly contexts. This paper aims to explore the basics of academic writing in English. It briefly discusses its major characteristic features, basic conventions, the politics of academic language and its spirit. The findings suggest that academic writing is a rigorous, evidence-based process that parallels scientific inquiry, fostering knowledge, promoting logical reasoning, and addressing the interplay between linguistic diversity and the dominance of English in academia.